2016
DOI: 10.1016/j.ssi.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Ionic transport modification in proton conducting BaCe0.6Zr0.3Y0.1O3−δ with transition metal oxide dopants

Abstract: Proton conducting BaCe0.6Zr0.3Y0.1O3-δ (BCZY63) pellets were fabricated by the solid-state reactive sintering method whereby a small extra amount of a metal oxide additive (5 mol%) was included in the precursor mixture before sintering. The effect of the addition of six different metal oxide additives (CuO, ZnO, Fe2O3, MnO2, PdO, and Cr2O3) on the transport properties of BCZY63 was investigated. Although most additives (e.g. ZnO, Fe2O3, MnO2, Cr2O3) led to a decrease (sometimes minor) in conductivity, CuO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…A is the area of the sample; L is the thickness of the sample; k is the Boltzmann's constant; and e is the electron charge. It is generally believed that the arc in the high-frequency region exhibits a value for the proton-conducting oxide grain (C =~10 −11 F), and that the arc in the intermediate-frequency region exhibits a value for the grain boundary (C =~10 −9 F) [6][7][8]13,30,31] that is in agreement with this study. The bulk dielectric constants of BZY obtained in this study were higher than those (37-155) reported in the literature [13,31,33,34].…”
Section: Electrochemical Properties Of Bazr 08 Y 02 O 3−δsupporting
confidence: 91%
See 1 more Smart Citation
“…A is the area of the sample; L is the thickness of the sample; k is the Boltzmann's constant; and e is the electron charge. It is generally believed that the arc in the high-frequency region exhibits a value for the proton-conducting oxide grain (C =~10 −11 F), and that the arc in the intermediate-frequency region exhibits a value for the grain boundary (C =~10 −9 F) [6][7][8]13,30,31] that is in agreement with this study. The bulk dielectric constants of BZY obtained in this study were higher than those (37-155) reported in the literature [13,31,33,34].…”
Section: Electrochemical Properties Of Bazr 08 Y 02 O 3−δsupporting
confidence: 91%
“…Therefore, in the present study, proton conductivity was measured under a reducing wet atmosphere (3% H 2 in Ar and pH 2 O = 0.03 atm). Cole-Cole plots are typically used to determine the grain (R b and CPE b ), grain boundary (R gb and CPE gb ), and electrode (R elec and CPE elec ) contributions [6][7][8]13,30,31]. Figure 6 shows the Cole-Cole plots obtained for the sintered BZY samples.…”
Section: Electrochemical Properties Of Bazr 08 Y 02 O 3−δmentioning
confidence: 99%
“…From the macroscopic viewpoint, the grain boundary resistance of the electrolytes can be reduced by increasing the grain size or decreasing the grain boundary density. There are two well‐known strategies to facilitate the grain growth such as the use of nanosized materials with enhanced sinterability or the addition of sintering additives . Both of these methods are useful for developing high‐efficient electrochemical devices.…”
Section: Functional Materials Of Proton‐conducting Socsmentioning
confidence: 99%
“…The proton reduction reaction to hydrogen is the rate-determining step in the hydrogen evolution reaction [43]. The slight amount of Ni doping in the BCZY phase enhances the electronic conductivity while maintaining the proton conductivity [31][32][33][34], which led to the enhancement of the current densities obtained using the Ni/BCZYN (x = 0.03) CLs. Moreover, in earlier papers, Ni dispersed on mixed conductors was found to lead to enhancement of the ERZ around the Ni catalyst particles with increasing electronic conductivity [24][25][26].…”
Section: Performances Of Ni/bczyn Clsmentioning
confidence: 99%
“…The CCL of µm-sized Ni-MPEC oxide cermet is formed on top of the CL to supply a highly electronically conductive layer, with high gas-diffusion rate from the separator (interconnect) to the CL, and an intimate contact between the separator and the CL. The slight amount of Ni doping in the proton-conducting oxide enhanced the electronic conductivity in the oxide [31][32][33][34], which was one of the most promising MPEC oxides for applications based on the above concept.…”
Section: Introductionmentioning
confidence: 99%